Notice of an Earthen Jar, found in excavating the foundation of an old house in Leith - Paterson, Robert (Proceedings of the Society of Antiquaries of Scotland, 1863)
The author describes a clay jar found in Leith. Although he compares it to Roman examples, he argues that this item is most likely a medieval wine vessel created in Leith at some point between the twelfth and sixteenth centuries.